Road Accidents in Nepal: Trends, GDP Impact, and Policy Gaps - Khanal, Krishna Prasad (Journal of Multidisciplinary Research Advancements, 2025)
This study examines the relationship between road accidents and gross domestic product (GDP) in Nepal, analysing trends from 1993 to 2018. Using descriptive statistics and econometric modelling, the research reveals that Nepal experiences an average of 5,239 road accidents annually, with motorcycles (37% of incidents) and pedestrians (39% of fatalities) being the most vulnerable. The multiple regression analysis demonstrates a significant negative impact of road accidents on GDP (β = -0.19, p < 0.01), indicating that a 1% increase in accidents reduces GDP growth by 0.14%. The study identifies key contributing factors, including poor road infrastructure (only 43% paved), inadequate maintenance, and weak policy enforcement. These findings underscore road safety as a public health priority and economic imperative, with recommendations for infrastructure investment, vehicle safety regulations, and improved data systems. The research provides empirical evidence for policymakers to integrate road safety measures into Nepal's economic development strategy, offering insights relevant to similar developing nations facing transportation challenges.